The EURO-FORTA (Fit fOR The Aged) list version 2: consensus validation of a clinical tool for improved pharmacotherapy in older adults - Pazan, Farhad; Weiß, Christel; Wehling, Martin (Drugs & aging, 2023)
The aging of our societies leads to a higher prevalence of multimorbidity and therefore polypharmacy, which often results in inappropriate drug treatment. To address this issue, numerous listing approaches, such as the Fit fOR The Aged (FORTA) list have been developed. FORTA’s positive impact on the quality of medications and relevant clinical outcomes has been shown. Based on new emerging evidence and experiences with the existing FORTA lists, we aimed to update the FORTA lists in several European countries/regions.
Online veröffentlicht: 2. Mai 2023
Gesehen am 16.09.2024